Porcine detection and methods thereof. - Che Man, Yaakub; Mustafa, Shuhaimi; Khairil Mokhtar, Nur Fadhilah (2010)

(untitled)
The present invention describes pork-specific real-time PCR assay is developed for Halal authentication. Meat samples are employed, which were pork, beef, chevon, mutton, venison and chicken. DNA from each raw meat sample was successfully extracted prior to real-time PCR reaction. PCR. In this context, the method would be useful in the highly sensitive detection of porcine DNA in edible and non-edible products.